Effect of Dosage of Bokashi Organic Fertilizer on Agronomic Growth and Productivity of Rice Plants (Oryza sativa) - Burhan Efendi; Haryono Haryono; Ivonne Fitri Mariay; Liz Yanti Andriyani; Amelia S. Sarungallo (West Science Agro, 2024)
This systematic literature review examines the effects of Bokashi organic fertilizer dosage on rice plants' agronomic growth and productivity (Oryza sativa). Using 16 Scopus-indexed articles, the study synthesizes findings on how Bokashi impacts key agronomic parameters such as plant height, tiller number, biomass production, and grain yield. The review highlights that optimal dosages (5–10 tons/ha) consistently improve growth and yield outcomes compared to chemical fertilizers or untreated controls. Bokashi's nutrient-rich composition and ability to enhance soil health and microbial activity make it a sustainable alternative for rice cultivation. However, its effectiveness depends on soil type, environmental conditions, and rice variety. Challenges related to dosage standardization and large-scale implementation are identified, and recommendations for future research are provided. This review underscores the potential of Bokashi in promoting sustainable agriculture while reducing reliance on synthetic inputs.